PENERAPAN TEORI ARSITEKTUR ORGANIK DALAM STRATEGI PERANCANGAN PUSAT PENGEMBANGAN INDUSTRI KREATIF DI BANDUNG - Song Prasetya Sujanra; Ummul Mustaqimah; Agung Kumoro Wahyu (ARSITEKTURA, 2017)
Creative economy is becoming an important aspect for our future economy because it is based knowledge and creativity, which are renewable resources. Creative economy needs good quality of creative human resources (creative class) to improve. Indonesia has a huge number of population with 70% of total are working-aged population which are potential in promoting creative economy, yet, Indonesia’s creative industry still can’t compete globally. Some strategies are needed to improve the quality and the quantity of creative class in Indonesia. One of the strategies is by providing creative environment with creative space as medium. A well-designed space can increase motivation, expand creative tempo, entertains and inspires. Creative space should provide attention, stimulation and focus. To achieve such characteristics, Organic Architecture is considered as the right design approach. Organic Architecture principals are used in designing strategy, such as in site analysis, spatial analysis, mass organization, mass transformation and façade programming. Analytical process applying Organic Architecture principals produces the design of creative hub building that optimizes the creative process.